Wiseguys and the White House : gangsters, presidents, and the deals they made - Dezenhall, Eric (Harper, 2025)
Wiseguys and the White House explores the influence of the mob on presidential power throughout American history. The book examines instances where connections between gangsters and presidents have shaped political outcomes and decisions. From Franklin Delano Roosevelt to Richard Nixon to Joe Biden, the mob has been involved in various activities such as assisting with political campaigns, carrying out covert operations, and influencing presidential actions. Key events include deals with mobsters like Lucky Luciano during World War II, the Chicago Outfit's role in John F. Kennedy's election, and the use of mob figures by presidents such as LBJ and Reagan. The book delves into the relationships between mobsters and political leaders, drawing on newly released government records and firsthand accounts to provide a detailed look at these often-hidden connections.